Performance of the CSM-CERES-Rice model in evaluating growth and yield of rice in the farm level - Phakamas, N. (International Journal of Agricultural Technology, 2015)
Crop simulation model becomes a useful tool in agricultural research. Its performance has been validated mostly by the experiments conducted by researchers in experimental stations, and the information on the performance of the model under farm conditions is rare. The objective of this study was to test the performance of the CSM-CERES-Rice model for evaluation of growth and yield of rice using farmer’s field data. The simulation was carried out using the management practices of the farmers as input data. The simulated values were in good agreement with observed values for days to flowering, days to physiological maturity and top dry weight of rice, whereas the associations between simulated values and observed values were rather poor for grain yield and harvest index. The poor associations between observed values and simulated values for grain yield and harvest index was due largely to high infestation of insect pests. CSM-CERES-Rice model can be used with some degree of accuracy to predict growth and yield of rice under growing conditions that are practiced by farmers in case of no severe infestation of insect pests and diseases. The model may be used for policy making by the government and decision making to produce rice by farmers.